Tuning delay differentiation in IP networks using priority queueing models - Sousa, Pedro (2002)
This article evaluates the use of Priority Queueing models to achieve delay differentiation in IP networks operating under the Class of Services paradigm. Three models are considered: proportional model, additive model and a novel hybrid schema based on the upper time limit model. The characteristics, behaviour and viability of these models are analysed as regards traffic delay differentiation. The impact of each model on traffic aggregation and on individual flows is also evaluated. This study is complemented by the analysis of delay differentiation from an end-to-end perspective. An adaptive differentiation mechanism is also proposed and discussed.